SYSTEMATIC LITERATURE REVIEW: EFEKTIVITAS PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP LITERASI NUMERASI - Amaliyah, Nezla; Nindiasari, Hepsi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the importance of numeracy literacy in mathematics learning and the need for an approach that can connect mathematical concepts with real-life situations. Based on previous research findings, this study aims to analyze the effectiveness of the Realistic Mathematics Education (RME) approach on students' numeracy literacy and to identify the factors influencing it. The method used is a Systematic Literature Review (SLR) to synthesize research results systematically, referring to the PRISMA principles to ensure the article selection process is conducted in a structured and transparent manner. Data were obtained from 11 scientific articles indexed in Sinta and Scopus, published between 2021 and 2026. The research results show that RME is effective in improving students' numeracy literacy thru enhanced conceptual understanding, critical thinking skills, and problem-solving abilities. The effectiveness is influenced by learning strategies and the use of supportive media. Moreover, the analyzed research is dominated by a quantitative approach with a focus on learning outcomes. Thus, RME is a relevant and effective approach in improving students' numeracy literacy